Effect of fatigue on the swimming event in high level pentathletes. Epée fencing influence on swimming performance - Demarie, S.; Magini, V.; Galvani, C.; Bianco, M. (Medicina dello Sport, 2011)
Aim. Modern Olympic Pentathlon tournament comprises five sport disciplines and extends over long duration. It is likely that the residual effect of prior exercise creates physiological responses that differ from performing each discipline as a distinct event. Purpose of the present study was to examine the effect of epée fencing (EF) on subsequent swimming performance.